Scribal Practice and the Global Cultures of Colophons, 1400–1800
XIX, 303 p. 142 illus., 31 illus. in color.
Keywords: “This is a tour de force of sophisticated global erudition.” —Filippo de Vivo, University of Oxford, UK “In its wide global range and rich variety of studies, this expertly edited volume provides an unprecedented view into the scribal practices of diverse cultural traditions in the early modern period.” —Johanna Drucker, University of California, Los Angeles, USA “This volume finally gives the colophon the place it deserves. We see scribes and printers at work in Thailand, the Deccan, Delhi, Damascus, Antwerp, and Timbuktu.” —Konrad Hirschler, University of Hamburg, Germany “In this cross-disciplinary endeavor, ten authors tell lively and exciting stories of historical scribal practices.” —Verena Klemm, University of Leipzig, Germany This book is the first to chart the global diversity of colophons between 1400 and 1800. The volume presents a new approach to scribal cultures that expands traditional definitions. Moving from the paradigm of codicological information towards a thorough interpretation of the wider social worlds of colophons in Africa, Asia, Europe, and North America, this volume uncovers the fascinating cultural history of early modern scribes. Chapters examine how those engaging in the composition and distribution of colophons shaped scribal identities, group cultures and bookish communities in a world in which manuscripts mattered. Authors build on approaches from anthropology, cultural studies, codicology, history, and philology to offer a new conceptual framework that studies colophons as scribal practices embedded in their changing social and cultural worlds. As a new contribution to the history of the book, this volume’s global approach pushes the boundaries of what constitutes a colophon.